USGS44, a new high‐purity calcium carbonate reference material for δ13C measurements. (7th January 2021) - Qi, Haiping; Moossen, Heiko; Meijer, Harro A.J.; Coplen, Tyler B.; Aerts‐Bijma, Anita T.; Reid, Lauren; Geilmann, Heike; Richter, Jürgen; Rothe, Michael; Brand, Willi A.; Toman, Blaza; Benefield, Jacqueline; et al.
Abstract : Rationale: The stable carbon isotopic ( δ 13 C) reference material (RM) LSVEC Li2 CO3 has been found to be unsuitable for δ 13 C standardization work because its δ 13 C value increases with exposure to atmospheric CO2 . A new CaCO3 RM, USGS44, has been prepared to alleviate this situation. Methods: USGS44 was prepared from 8 kg of Merck high‐purity CaCO3 . Two sets of δ 13 C values of USGS44 were determined. The first set of values was determined by online combustion, continuous‐flow (CF) isotope‐ratio mass spectrometry (IRMS) of NBS 19 CaCO3 ( δ 13 CVPDB  = +1.95 milliurey (mUr) exactly, where mUr = 0.001 = 1‰), and LSVEC Li2 CO3 ( δ 13 CVPDB  = −46.6 mUr exactly), and normalized to the two‐anchor δ 13 CVPDB‐LSVEC isotope‐delta scale. The second set of values was obtained by dual‐inlet (DI)‐IRMS of CO2 evolved by reaction of H3 PO4 with carbonates, corrected for cross contamination, and normalized to the single‐anchor δ 13 CVPDB scale. Results: USGS44 is stable and isotopically homogeneous to within 0.02 mUr in 100‐μg amounts. It has a δ 13 CVPDB‐LSVEC value of −42.21 ± 0.05 mUr. Single‐anchor δ 13 CVPDB values of −42.08 ± 0.01 and −41.99 ± 0.02 mUr were determined by DI‐IRMS with corrections for cross contamination. Conclusions: The new high‐purity, well‐homogenized calcium carbonate isotopic reference material USGS44 is stable and has a δ 13 CVPDB‐LSVEC value of −42.21 ± 0.05 mUr for both EA/IRMS and DI‐IRMS measurements. As a carbonate relatively depleted in 13 C, it is intended for daily use as a secondary isotopic reference material to normalize stable carbon isotope delta measurements to the δ 13 CVPDB‐LSVEC scale. It is useful in quantifying drift with time, determining mass‐dependent isotopic fractionation (linearity correction), and adjusting isotope‐ratio‐scale contraction. Due to its fine grain size (smaller than 63 μm), it is not suitable as a δ 18 O reference material. A δ 13 CVPDB‐LSVEC value of −29.99 ± 0.05 mUr was determined for NBS 22 oil.